The influence of quality, reputation, social media marketing, emotional value, spiritual value, and word of mouth on intention to enroll in private schools - Rantedoping, Rama; Wuisan, Dewi Sri Surya (Enrichment : Journal of Management, 2025)
The study aims to analyze the factors that influence parents' intentions in choosing private schools for their children in and around Jakarta. The research method used is quantitative, with surveys conducted through the distribution of online questionnaires. The factors analyzed included spiritual value, quality, reputation, social media marketing, emotional value, and word of mouth. The results of a study with 180 respondents using PLS-SEM showed that all these factors had a significant influence on parents' intentions to enroll their children in private schools. Based on IPMA analysis, emotional value factors have the strongest influence, followed by reputation, social media marketing, word of mouth, spiritual value, and quality. The managerial implications of this study emphasize the importance of focusing on activities that enhance positive emotions, strengthening reputation, quality of service, and effective marketing strategies. The research has made important contributions to understanding the factors that influence parents' intentions in choosing private schools, as well as providing insights for private schools to focus on these factors in order to increase parents' interest in selecting their schools